WILLIAM JAMES: THE CONCEPTION OF PRAGMATISM - Vytis Valatka (Problemos)
The conception of Pragmatism, raised by William James, encloses two fundamental components: the pragmatic method of cognition and the pragmatic conception of truth. The pragmatic method affirms that we must investigate only those ideas, conceptions, theories, etc., that can be put to the test of current human experience. The pragmatic conception of truth asserts that ideas, confirmed by the means of the above mentioned experience, must be regarded as true. These true ideas always bear the aspects of might and practical use, in so far as they serve as certain ways to take possession of the world of our external or internal experience. The truth of idea, conception, theory, etc., can not, however, be reduced to its practical utility. A true idea always bears an aspect of correspondence to reality. It either corresponds to the world of our external experience (as the ideas of natural sciences do), or to the world of our internal experience (as metaphysical ideas do).